Undergraduate Nursing Students’ Attitudes towards Mental Illness: Implications for Specific Academic Education - Poreddi, Vijayalakshmi (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Health care professions are not immune to social prejudices and surprisingly share the general public's attitude attributed to people with mental illness. Nursing students are future health manpower research related to nursing students attitudes toward mental illness is limited. AIM: The aim of this following study is to examine the undergraduate nursing students’ attitudes toward people with mental illness. MATERIALS AND METHODS: Cross-sectional descriptive design was adopted for the present study. A total of 148 undergraduate nursing students were purposively selected to complete self-reported questionnaires. RESULTS: The nursing students have significant positive attitudes towards mental illness in three of the six attitudes factors: Restrictiveness (8.59), benevolence (29.8) and stigmatization (9.18). However, these students have negative attitudes in separatism (27.1), stereotype (11.5) and pessimistic predictions (11.7) domains as they rated high. CONCLUSION: Academic education in this area must be planned so as to favor the change of the attitudes that include greater use of teaching strategies that challenge beliefs and assumptions and promote a commitment to provide holistic care to people with mental illness.